2021
DOI: 10.1246/bcsj.20210192
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic and Photothermal Effects of Carbon Dot-Coated Magnetite- and Porphyrin-Conjugated Confeito-Like Gold Nanoparticles

Abstract: Gold nanoparticles (AuNPs) possess the characteristics of both inertness and biocompatibility which enable great biomedical application in biosensors and drug delivery. Confeito-like AuNPs conjugated with porphyrin (TCPP) were synthesized and characterized to clarify the photodynamic and photothermal properties. The conjugation of TCPP was performed by covalent binding using L-cysteine or carbon dot-protected iron oxide (Fe3O4@Cdots) as adapted linkages. The product had a great aptitude for photosensitization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The latter values calculated using eq increased in the order of Au nanoparticle (AuNP) < Fe 3 O 4 NP@carbon dot (Cdot) < AuNP/Fe 3 O 4 NP@Cdot < porphyrin derivative (TCPP) < AuNP/TCPP < AuNP/Fe 3 O 4 NP@Cdot/TCPP and with their concentration. Thus, the highest value (20 mmol/g­(material)) was obtained for AuNP/Fe 3 O 4 NP@Cdot/TCPP at a 10 μg/mL concentration . This value was smaller than the current CNH-based generators.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…The latter values calculated using eq increased in the order of Au nanoparticle (AuNP) < Fe 3 O 4 NP@carbon dot (Cdot) < AuNP/Fe 3 O 4 NP@Cdot < porphyrin derivative (TCPP) < AuNP/TCPP < AuNP/Fe 3 O 4 NP@Cdot/TCPP and with their concentration. Thus, the highest value (20 mmol/g­(material)) was obtained for AuNP/Fe 3 O 4 NP@Cdot/TCPP at a 10 μg/mL concentration . This value was smaller than the current CNH-based generators.…”
Section: Resultsmentioning
confidence: 74%
“…Moreover, the tendency for 1 O 2 production is in proportion to the O 2 uptake in carriers except for GO (Figure A). The 1 O 2 production capabilities have been reported for different generators using different detection techniques, such as UV–visible absorption spectroscopy, fluorescence, ,, and electron paramagnetic resonance . Moreover, its quantitative evaluation depended on the evaluation technology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Imahori et al reported the fluorescence lifetime of porphyrin adsorbates on AuNPs was significantly longer than those on a two-dimensional Au substrate ( Imahori et al, 2001 ). The general strategy for the adjustment of photophysical properties of dye–AuNP conjugates involves altering the size and shape of the nanoparticles and the length of the linkers ( Imahori et al, 1998 ; Dulkeith et al, 2005 ; Hong and Li, 2013 ; Do and Imae, 2021 ). However, less attention has been paid to the number of adsorbates loaded per particle, despite the strong influence on photophysical properties ( Shinohara and Shinmori, 2016 ).…”
Section: Introductionmentioning
confidence: 99%